Ultrafast photochemistry of a molybdenum carbonyl-nitrosyl complex with a triazacyclononane coligand - Gessner, Niklas; Baeck, Anna K.; Knorr, Johannes; Nagel, Christoph; Marquetand, Philipp; Schatzschneider, Ulrich; Gonzalez, Leticia; Nuernberger, Patrick (Physical Chemistry Chemical Physics, 2021)
Transition metal complexes capable of releasing small molecules such as carbon monoxide and nitric oxide upon photoactivation are versatile tools in various fields of chemistry and biology. In this work, we report on the ultrafast photochemistry of [Mo(CO)(2)(NO)(iPr(3)tacn)]PF6 (iPr(3)tacn = 1,4,7-triisopropyl-1,4,7-triazacyclononane), which was characterized under continuous illumination and with femtosecond UV-pump/UV-probe and UV-pump/MIR-probe spectroscopy, as well as with stationary calculations. The experimental and theoretical results demonstrate that while the photodissociation of one of the two CO ligands upon UV excitation can be inferred both on an ultrafast timescale as well as under exposure times of several minutes, no evidence of NO release is observed under the same conditions. The binding mode of the diatomic ligands is impacted by the electronic excitation, and transient intermediates are observed on a timescale of tens of picoseconds before CO is released from the coordination sphere. Furthermore, based on calculated potential energy scans, we suggest that photolysis of NO could be possible after a subsequent excitation of an electronically excited state with a second laser pulse, or by accessing low-lying excited states that otherwise cannot be directly excited by light.
CRIS-Team WoS Importer:2021-11-05